The August Krogh Institute: Capillaries and beyond. (10th October 2015) - Sjøgaard, G.
Abstract : Bengt Saltin knew very well the history and work of the giants whose shoulders he was standing upon, such as August Krogh and Johannes Lindhard. He was basically a physiologist interested in physical activity and exercise, particularly in the cardiovascular and muscular responses. Some of his major original contributions were (a) the human muscle model in terms of the one‐legged, knee extensor quantifying work by the high‐precision Krogh ergometer and, using this, challenging Krogh's proposed autoregulation of capillary blood flow during exercise; (b) the electrolyte fluxes quantification on an intra‐ and extra‐cellular level in human muscle during exercise to reveal such changes as possible fatigue mechanisms; and (c) the evidence presented that underlined the health‐enhancing effect of physical exercise training from bedside to workplace.